La promotion de l'équité en éducation sexuelle dans les écoles secondaires de la région d'Ottawa - Martinez, Andrea; Phillips, Karen (Canadian Journal of Education/Revue canadienne de l'éducation, 2009)
Cet article examine les représentations sociales de l’équité en santé sexuelle à partir de données d’entrevues auprès de 30 enseignantes et enseignants des écoles secondaires de la région d’Ottawa, incluant cinq municipalités périphériques de l’est et du centre‐est ontariens.Partant d’un cadre d’interprétation féministe des principaux écueils des interventions en éducation sexuelle, notamment l’âgisme, le naturalisme, l’essentialisme, l’hétérosexisme et l’ethnocentrisme, l’analyse révèle l’omniprésence d’une conception biomédicale de la sexualité qui, nourrie par l’imaginaire du risque, parvient difficilement à rompre les résistances en matière de plaisir, d’autoérotisme et d’intégration des différences sexuelles, « raciales » ou ethniques.
https://journals.sfu.ca/cje/index.php/cje-rce/article/view/3035/2323
Keywords: 2000 à aujourd'hui; 2000-2009; EDI; amérique du nord; amériques; approches et analyses; canada; discipline; hétérosexisme; ontario; ottawa; périodes historiques; ressource en ligne; régions géographiques; santé; santé sexuelle; science de l'éducation; sexualité; systèmes d'oppressions; thématiques; éducation sexuelle; étude qualitative

Transformative conversations about sexualities pedagogy and the experience of sexual knowing - Trimble, Lisa (Sex Education : Sexuality, Society and Learning, 2009)
One of the hallmarks of sex education traditionally has been its Cartesian endorsement of mind/body dualism; we have preferred to equate ‘self’ as synonymous with ‘mind’, and have invested heavily in believing in the valence of rationality‐based sexualities education. We generally do not consider the way ‘self’ negotiates, interprets and relates to sexual knowledge in all of our complexity, including our messy, embodied and emotional lives. In this paper I address what I think are several much‐needed conversations for a holistic pedagogy of sexualities to incorporate, including the falseness of the mind/body split, reconsidering what counts as sexual knowledge, the role of the performative in communicating our sexual knowing, and the importance of considering affect in learning about sexualities. The second part of the paper examines pedagogical considerations currently absent in dialogues of sexualities education, such as incorporating transformational learning strategies in teaching sexualities, and what it means to educate toward being a sexual citizen. Finally, I will outline how discussions of epistephenomenology (our relationship to and how we experience knowledge) can contribute to moving toward a vision of a critical, cultural sexualities education.
Number: 1
Keywords: approches et analyses; corps; discipline; discours dominant; phénoménologie; ressource en ligne; savoir expérientiel; science de l'éducation; sciences humaines; sexualité; systèmes d'oppressions; thématiques; éducation sexuelle; émotions; épistémologie